1999
DOI: 10.1074/jbc.274.3.1519
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression and Functional Characterization of a Mouse Renal Organic Anion Transporter in Mammalian Cells

Abstract: Organic anion transporters play an essential role in eliminating a wide range of organic anions including endogenous compounds, xenobiotics, and their metabolites from kidney, thereby preventing their potentially toxic effects within the body. The goal of this study was to extend our previous study on the functional characterization and posttranslational modification of a mouse kidney organic anion transporter (mOAT), in a mammalian cell system, COS-7 cells. The transporter-mediated p-aminohippurate (PAH) upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
63
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 24 publications
6
63
0
Order By: Relevance
“…1A). This is consistent with previous studies showing that coincubation of mOat1-transfected oocytes with unlabeled PAH resulted in dosedependent inhibition of uptake of labeled PAH with an estimated K i of 13 M (11), which is similar to previously reported values for the affinity of PAH for mOat1 (22). In comparison, ES inhibited tracer uptake with an IC 50 value for mOat3 of 8 Ϯ 2 M (Fig.…”
Section: Resultssupporting
confidence: 81%
“…1A). This is consistent with previous studies showing that coincubation of mOat1-transfected oocytes with unlabeled PAH resulted in dosedependent inhibition of uptake of labeled PAH with an estimated K i of 13 M (11), which is similar to previously reported values for the affinity of PAH for mOat1 (22). In comparison, ES inhibited tracer uptake with an IC 50 value for mOat3 of 8 Ϯ 2 M (Fig.…”
Section: Resultssupporting
confidence: 81%
“…(Expression of mouse OAT1 in oocytes was induced by microinjection of the corresponding in vitro transcribed cRNA.) As expected, co-incubation of oocytes with unlabeled PAH resulted in dosedependent inhibition of uptake of labeled PAH, with an estimated K i of ϳ13 M (this is similar to previously reported values for the affinity of PAH for OAT1 (28,69)). …”
Section: Renal Excretion Of Organic Anions In Vivo-supporting
confidence: 68%
“…Although several OAT isoforms have been isolated to date, information of the function of each isoform is still not sufficient. Moreover, the functional property of mouse OAT homologs is limited despite the fact that mouse OAT1 (mOAT1) (NKT) and mouse OAT3 (mOAT3) (Roct) isoforms have been isolated (Lopez-Nieto et al, 1997;Brady et al, 1999;Kuze et al, 1999). Among the OAT isoforms, only OAT2 is predominantly expressed in the liver, and this isoform is considered one of the key molecules in hepatic handling of organic anions.…”
mentioning
confidence: 99%
“…OAT1 has a broad substrate specificity and interacts with a wide range of organic anions such as p-aminohippuric acid (PAH), dicarboxylates, cyclic nucleotides, prostaglandin E 2 (PGE 2 ) (Sekine et al, 1997;Sweet et al, 1997;Apiwattanakul et al, 1999). Subsequently, OAT1 orthologs have been isolated from humans and mice (LopezNieto et al, 1997;Hosoyamada et al, 1999;Kuze et al, 1999;Lu et al, 1999;Race et al, 1999). So far, four additional members belonging to the organic anion transporter family, OAT2 (Simonson et al, 1994;Sekine et al, 1998), OAT3 (Kusuhara et al, 1999;Race et al, 1999;Cha et al, 2001), OAT4 (Cha et al, 2000), and OAT5 (Sun et al, 2001), have been cloned and identified.…”
mentioning
confidence: 99%